ANALISIS KERUSAKAN POMPA HIDROLIK PADA EKSKAVATOR R 330LC-9S (STUDI KASUS DI RENTAL ALAT BERAT YOGYAKARTA) - Juan Pratama Aditya; Danar Susilo Wijayanto; Towip Towip (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
The purpose of this study is to: 1) Analyse the factors affecting the damage of medium-sized excavator pumps with type 330LC-9s; and 2) analyse the impact of pump damage on medium-scale excavators with Type 330L C-9s. This type of research is qualitative with purposive sampling techniques. The population of the sample of this research was an employee in the rental workshop of excavators, with with a sample chief mechanic, expert technician, and three operators. The researchers conducted active participation observations. The results of this study are: 1) The factors causing the failure of the hydraulic pump excavators R 330LC-9s are the lack of attention of operators in operations in the field, the use of instruments that do not match their capacity, a lack of periodic service, and mechanical repairs that are not in accordance with procedures. 2) When the hydraulic pump excavators R 330LC-9s have problems, they become low-power, so noise and operational function are not at their maximum. So we need to replace spare parts, replace oil, and regularly maintain both mechanically and procedurally.